"It's Simply Integral to What I Do": Enquiries into how the web is Weaved into Everyday Life - Lindley, Siân; Meek, Sam; Sellen, Abigail; Harper, Richard (Proceedings of the 2012 international conference on World Wide Web, 2012)
This paper presents findings from a field study of 24 individuals who kept diaries of their web use, across device and location, for a period of four days. Our focus was on how the web was used for non-work purposes, with a view to understanding how this is intertwined with everyday life. While our initial aim was to update existing frameworks of ‘web activities’, such as those described by Sellen et al. [25] and Kellar et al. [14], our data lead us to suggest that the notion of ‘web activity’ is only partially useful for an analytic understanding of what it is that people do when they go online. Instead, our analysis leads us to present five modes of web use, which can be used to frame and enrich interpretations of ‘activity’. These are respite, orienting, opportunistic use, purposeful use and lean-back internet. We then consider two properties of the web that enable it to be tailored to these different modes, persistence and temporality, and close by suggesting ways of drawing upon these qualities in order to inform design.